IMPLEMENTASI PROGRAM INDONESIA PINTAR DI SD NEGERI SUKACAI, KABUPATEN SERANG - setiawan, hary; ode, samsul (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2019)
Program Indonesia Pintar is a national program that aims to remove impedimentsfor school by helping poor students to gain access to a decent education services,preventing dropout, encourage poor students to go back to school, help students to fulfill the needs in learning activities,the purpose of this research is to determine how the implementation ofProgram Indonesia Pintar at SD NegeriSukacai 3 Sub-district Baros, Serang Regency running. Formulation of the problem of the research is to find out the implementation of the Program Indonesia Pintar at SDN Sukacai 3 and whether the implementation has been right on target or notThis research used descriptive qualitative research method. The informants of this research consisted of technical implementation unit of education agency (UPTD) of Sub-district Baros, principal of SDN Sukacai 3, staff of SDN Sukacai 3, parents of students and officers of BRI Unit Baros. Researcher used purposive technic for choosing the informants.The result of the research shows that the implementation of Program Indonesia Pintarat SDN Sukacai 3already well underway, viewed from various aspects such as communication, resources, disposition and the bureaucratic structure. Distribution of the grant-in-aid of Program Indonesia Pintarat SD NegeriSukacai 3 is already on targetwhere the information has reached the recipient policies,which are the parents of students.